2012
DOI: 10.1097/aap.0b013e31823e77d5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Obturator Nerve Block

Abstract: In ultrasound-guided obturator nerve block performed after the division of the nerve, injection of local anesthetic between the planes of the adductor muscles is comparable to nerve stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…This difference was statistically significant ( P < 0.05). Our results are in congruence with Manassero et al .,[16] who observed a longer block performance time in the USENS group than in the US group (3.0 vs. 1.6 min) while performing ONB. An almost similar time of 2 min has been reported by Sinha et al .,[22] in their study, using US-guided ONB without nerve stimulation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This difference was statistically significant ( P < 0.05). Our results are in congruence with Manassero et al .,[16] who observed a longer block performance time in the USENS group than in the US group (3.0 vs. 1.6 min) while performing ONB. An almost similar time of 2 min has been reported by Sinha et al .,[22] in their study, using US-guided ONB without nerve stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…The ON is one such nerve that can be both, difficult to stimulate electrically and image sonographically. [16] Stimulation of the ON by electric current during TURBT causes sudden jerk (obturator reflex) due to contraction of adductor muscles. This may lead to bladder perforation or deep cut causing profuse bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Manassero and colleagues (11) in Italy showed that ultrasound-guided obturator nerve block may be performed after the division of the nerve and the injection of local anesthetic between the planes of the adductor muscles is equal to nerve stimulation. Helayel et al (12), in Brazil among 22 subjects, demonstrated that ultrasound-guided obturator-nerve identification and block are technically easy and highly successful.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared sonographic identification of the obturator nerve versus neurostimulation techniques [23,24]. Techniques can be classified depending on whether the approach is distal or proximal.…”
Section: Obturator Nerve Block (Onb)mentioning
confidence: 99%